Comportamento em desgaste microabrasivo de superligas de cobalto produzidas por laser cladding e fundição - Ramos, Filipe Dondoni (2018)
Superalloys are materials usedin a variety of engineering applications in which wear and corrosion resistance, especially at high temperatures, are prime factors in the life of the equipment.Thesealloys are usually provided in the form of cast or forged alloys, but an economically viable option is the production of coatings of such superalloys on a substrate.The use of laser cladding technology has been highlighted as an alternative to produce these coatings, since the high solidification rates,in the order103-107K/s, associated to the process produce surfaces with highly refined microstructures, promoting the wear resistance of these coatingsmaterials, in addition to a low dilution.In the literature, there are several research that reports the tribological behavior of these superalloys in sliding, erosive and abrasive wear. However, there is still a lack of information on the behavior of these alloys in microabrasion.Specifically, cobalt superalloys are used in the manufacture of components present in the production of 2ndgeneration ethanol, in which about 8% of the material processed in the reactor is composed of hard abrasive particles, mainly silica, that cause abrasive wear of the components. In order to understand the tribological behavior of these materials inmicroabrasion, three cobalt-based superalloys known commercially as Stellite 1, 6 and 12 were deposited, using thelasercladding technology, on a castsubstrate of the Co30Cr19Fe alloy. The microabrasion tests were performedwith Al2O3, SiC and SiO2abrasives in a suspension of 0.1 g/cm3in distilled water. The test load was0.3 Nand rotational speed was20 rpm. Additionally, for comparison criterion, the alloy used as substrate and other castalloy with composition close to the Stellite 6 alloy were also tested. The statistical analysis of the wear coefficients using the ANOVA tool revealed that the wear coefficients of these materials are influenced by both the abrasive used in the test and the material tested. The Co30Cr19Fe alloy used as the substrate showed the highest wear rates, while the samples coated with the Stellite 1 alloy and the castalloy with composition close to Stellite 6 showed, in general, lower average coefficients of wear. Statistically, these last two materials presented equal average coefficients of wear.The predominant wear micromechanism was the grooving wear, except in the tests of the samples coated with Stellites 6 and 12, and that were tested with SiC abrasive, in which the mixed mechanism and the rolling mechanism, respectively, were predominant.The presence of secondary micromechanism of rolling wear was observed and associated with the granulometric distribution of abrasives. The analysis of severity allowed to understand the influence of the granulometric distribution of the abrasive particles in the wear, obtaining a better correlation between the experimentally observed mechanisms and the mechanisms predicted when this distribution was considered.